Counselor’s Knowledge, Attitude and Practice of Infant and Young Child Feeding (IYCF) Counselling - Syifa Fakhomah Syihab; Ayu Mutiara Santanu; Delita Septia Rosdiana; Isti Kumalasari (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Efforts to reduce the prevalence of undernutrition can be done with the proper IYCF practices. IYCF promotion and counseling activities for caregivers can increase the success of IYCF implementation and reduce the prevalence of malnutrition.Objectives: The objective of this study is to determine the association between the level of education, knowledge, and behavior of Posyandu counselors on IYCF practice in the Parongpong District of West Bandung Regency.Materials and Methods: This research is a cross-sectional study with a consecutive sampling technique. Descriptive analysis was conducted to describe the characteristics of the respondents, and the multivariate test was used to determine the variables meets the model equation.Results: Multivariable analysis showed that the variables that were significantly related to the practice of IYCF counseling were the level of education, knowledge, and behavior which were controlled by the confounding variable for the period of being a counselor.Conclusion: The level of education, knowledge, and behavior of Posyandu counselors in IYCF counseling practice is an important factor that can support the improvement of children's nutritional status.